Problematizing Ideas of Purity and Timelessness in the Conservation Narratives of Sacred Groves in Xishuangbanna, China - Zeng, Lily (Journal for the Study of Religion, Nature and Culture, 2018)
The recent promotion of sacred groves in conservation often assumes four problematic narratives of nature and culture based on ideas of purity and timelessness: (1) sacred groves are remnants of pristine forests; (2) nature is made sacred through the absence of human activity; (3) sacred groves are a-historical; and (4) sacred groves are removed from modernity. I problematize these narratives using ethnographic analyses of sacred groves protected by ethnic minority Dai communities in Xishuangbanna, a region containing China's richest biodiversity. I argue that the nature-culture divide inherent in conservation literature poorly describes sacred groves, which are dynamic entities integrated into modern Dai communities. Moreover, I contend that these narratives persist because they are deployed for political agendas by various outside actors (e.g., government, conservationists, tourism developers) and occasionally by Dai communities themselves during the co-production of landscapes, livelihoods, and identity corresponding to times of rapid transformation in a modern world.